Generation of Aryllithium Reagents from N-Arylpyrroles Using Lithium - Ozaki, Tomoya; Kaga, Atsushi; Saito, Hayate; Yorimitsu, Hideki (Synthesis, 2021)
Treatment of 1-aryl-2,5-diphenylpyrroles with lithium powder in tetrahydrofuran at 0 °C results in the generation of the corresponding aryllithium reagents through reductive C–N bond cleavage.
Keywords: organolithium reagents; C–N bond cleavage; lithium; pyrroles; metalation; reduction; deamination